A novel dual-signal electrochemical sensor for bisphenol A determination by coupling nanoporous gold leaf and self-assembled cyclodextrin. (1st May 2018) - Zhang, Ruyue; Zhang, Yang; Deng, Xiling; Sun, Shiguo; Li, Yingchun
Abstract: Bisphenol A (BPA) is an endocrine disrupting chemical, which can mimic estrogen and bring about a series of negative impact on human health. Herein, we developed a novel dual-signal sensor by coupling nanoporous gold leaf (NPGL) with thiolated beta-cyclodextrin (SH- β -CD) to realize sensitive and selective determination of BPA. Modification with NPGL and self-assembling of SH- β -CD on gold electrode were tracked by scanning electron microscopy, energy-dispersive spectroscopy and electrochemical measurements. The dual signaling method is based on the competitive host–guest interaction by recording the signals from both target molecule BPA and probe molecule methylene blue (MB). Due to the different binding ability of host molecule ( β -CD) towards BPA and MB, BPA is able to enter β -CD cavities and replace the pre-existing MB, resulting in the decreased oxidation peak current of MB and the increased oxidation peak current of BPA. The summation of both current changes (|Δ I MB | + Δ I BPA ) is linearly dependent on Napierian logarithm of BPA concentration from 3 × 10 −7  M to 1 × 10 −4  M with a detection limit of 6 × 10 −8  M (S/N = 3). It is noted that the detection limit obtained by dual-signaling is much lower than that using single Δ I BPA as the response signal. This newly developed sensor was further adopted to measure BPA in milk and tap water. The proposed dual-signal strategy and the established hybrid electrochemical sensor have great potential applications in biomarker detection, food safety testing and environmental monitoring. Graphical abstract: Highlights: A dual-signal strategy based on host-guest interaction was developed for BPA assay. The first report by coupling NPGL with CDs to make hybrid electrochemical sensor. Dual signaling was got by replacing the pre-existing MB in CD cavities with BPA. The detection limit is greatly decreased by using dual signaling (|Δ I MB | + Δ I BPA ).